Evaluation of the snow loads on the snow galleries on the Iron Ore Line in Northern Sweden - Saback, Vanessa; Gonzalez‐Libreros, Jaime; Daescu, Cosmin; Hojsten, Tommy; Sas, Gabriel (ce/papers, 2023)
The Iron Ore Line is a railway in northern Sweden and Norway, crucial for iron oretransportation. Snow galleries safeguard this route, ensuring uninterrupted trafficfor efficient operations. A snow gallery is a protective structure that shields roadsand railways from heavy snowfall and avalanches. Reported damages to these structures caused by excessive snow loads have prompted an investigation to preventfurther issues. This paper presents an analysis of the evolution of snow load calculations over time, though a comparison of Swedish design standards. The designsnow loads required by current standards have increased up to 60% from the initialregulations, depending on the location of the structure. Besides, climate change ispredicted to further increase snow loads due to more frequent winter precipitation,higher snow density, and extreme snowfall events. This analysis is part of a broaderresearch project involving numerical simulations, live monitoring, and a digital twinmonitoring system of some snow galleries in the Iron Ore Line. Godkänd;2023;Nivå 0;2023-10-02 (joosat);